Design and energy characteristic analysis of a flexible isobaric strain-energy compressed-air storage device. (June 2022) - Du, Hongwang; Bian, Xin; Xiong, Wei
Abstract: Considering the problems of traditional compressed-air storage devices, such as low energy efficiency, low energy density, and portability challenges, a flexible, isobaric strain-energy compressed-air storage device based on a hyperelastic rubber material was proposed. The device was composed of a flexible internal expandable rubber airbag and a rigid external shield. The main influencing factors of the charging and discharging processes of the gas storage device (peak pressure, expansion pressure, and contraction pressure) were explored and analyzed, and the effects of these factors on the pressure were verified. The fluctuation rates of the expansion and contraction pressures of the gas storage device were 0.5% and 0.4%, respectively, indicating that the gas storage device had good isobaric and stable energy storage and release characteristics. A mathematical model describing the energy storage efficiency of the device was developed based on the first law of thermodynamics. Furthermore, the charging and discharging characteristics of the device were tested. Experimental results showed that the average energy storage efficiency of the device reached 76.9%, and the volume energy density was 309.48 kJ/m 3, which is twice that of a traditional rigid gas storage tank. Highlights: A flexible isobaric strain energy compressed air storage device based on hyperelastic rubber material is proposed. The gas storage device has good isobaric and stable energy storage/release characteristics. The average energy storage efficiency of the device can reach 76.9%, and the volume energy density is 309.48 KJ/m 3 .